ONLINE PROJECT-BASED LEARNING IN COVID-19 PANDEMIC: EFL PRE-SERVICE TEACHER’ STORY - Arwanto, Harun; Ni'mah, Ana Mufidatun (Universitas Muhammadiyah Metro, 2023)
The study explored the experiences of a pre-service EFL teacher when participating in online project-based learning activities in critical listening class during the Covid-19 pandemic. The study aimed to investigate students' skills that can be developed through online project-based learning other than language skills and a female pre-service EFL teacher's perspectives on the benefits and challenges of using online project-based learning in English as a foreign language online class. The study employed a narrative inquiry model. The semi-structured interview and narrative frame were employed to collect the data. The result revealed that not only develop critical listening but such skills as technical skills in using technology for learning; self-learning; problem-solving; collaboration and communication with peers; critical and creative thinking; and time management outside the classroom can also be increased after joining online classes that implement project-based learning by using various learning platforms. In addition, implementing online project-based learning also provides several benefits and challenges for the participant